Communication During Palliative Care and End of Life: Perceptions of Experienced Pediatric Oncology Nurses. Issue 2 (March 2017) - Montgomery, Kathleen E.; Sawin, Kathleen J.; Hendricks-Ferguson, Verna
Abstract : Background: Communication between patients, families, and healthcare providers is a central component of end-of-life care. Nurse communication during palliative care (PC) and end of life (EOL) is a phenomenon with limited research. It is unclear how the level of nursing experience influences the perspectives of nurses communicating during EOL. Objective: The aim of this study is to describe the commonalities of experienced nurses' perceptions of communicating during PC and EOL and perceptions of barriers and facilitators to effective communication. Methods: This study was part of a larger multisite study that used a qualitative, empirical phenomenology design and represents focus group data gathered from pediatric oncology nurses with more than 5 years of experience or who were advanced practice nurses not involved in the direct evaluation of other nurses. Results: Five core themes with corresponding themes and subthemes were identified. The core themes included ( a ) Evolution of PC/EOL, ( b ) Skill of Knowing, ( c ) Expanded Essence of Caring, ( d ) Experienced Nurse as Committed Advocate, and ( e ) Valuing Individual Response to Grief. Conclusions: Findings reflect how the concept of experience transcended the 5 core themes and captured how experience provided nurses the know-how to fulfill the roles of communication, caring, and advocacy for children and families. Implications for Practice: Enhancing nurse communication skills during EOL requires opportunities to gain experience coupled with clinical strategies, such as standardized curricula, simulation, competency-based orientation programs, mentorship, and peer support.